Organoindium-modified monodisperse ellipsoid-/platelet-like periodic mesoporous silicas. Issue 23 (31st May 2017) - Liang, Yucang; Meixner, Martin
Abstract : Indium-modified mondisperse ellipsoid-/platelet-like large-pore periodic mesoporous silica nanoparticles (MMSNs) SBA-15 have been prepared via molecular grafting of In[N(SiMe3 )2 ]3 . Surface ligand exchange led to the formation of heteroleptic In species, and the resulting surface In species were converted into crystalline In2 O3 nanoparticles by calcination. Abstract : In this study, an indium(iii ) silylamide complex was respectively grafted onto monodisperse ellipsoid-like (E) and platelet-like (P) large-pore hexagonal periodic mesoporous silicas (PMSs) SBA-15 to afford hybrid materials In[N(SiMe3 )2 ]3 @SBA-15E and In[N(SiMe3 )2 ]3 @SBA-15P with well-defined surface species (SiO)2 In[N(SiMe3 )2 ], SiOIn[N(SiMe3 )2 ]2, and SiOSiMe3 . Surface ligand exchange between silylamido and alkoxyl group led to the conversion of surface species (SiO)2 In[N(SiMe3 )2 ] and SiOIn[N(SiMe3 )2 ]2 into (SiO)2 In(OR) and SiOIn(OR)2 (R = Me, Et, iPr) with donor ligands thf or NH3, respectively, revealing that silylamido coordinated to the indium centre could be completely exchanged with alkoxyl groups (–OMe, OEt or OiPr). Solid-state 1 H, 13 C and 29 Si nuclear magnetic resonance spectra and elemental analyses confirmed that surface species SiOIn[N(SiMe3 )2 ]2 are dominant in comparison with bipodal (SiO)2 In[N(SiMe3 )2 ] and SiOSiMe3 . The diffuse reflectance infrared Fourier-transform spectroscopy of In-modified hybrid materials directly evidenced the alteration of surface species before and after grafting of In[N(SiMe3 )2 ]3 and surface ligand exchange. In addition, the change of pore parameters (pore diameter, specific surface area and pore volume) monitored by nitrogen physisorption also indirectly corroborated the immobilization of the indium complex and the occurrence of ligand exchanges between –[N(SiMe3 )2 ]2 and –OR (R = Me, Et, iPr) on the surface of SBA-15. Note that the calcination of In-modified hybrid materials at 540 °C led to the formation of crystalline In2 O3 nanoparticles with different sizes which were respectively located in the internal pore and on the external surface of SBA-15 due to the pore confinement effect, migration effect and shape effect of the parent support, but the long-range ordered mesopore arrays were still preserved and the crystalline structures of In2 O3 were verified by powder X-ray diffraction and transmission electron microscopy.